9-3/1/3+1=

This expression is ambiguous because it’s not clear which operation should be performed first: should we divide 3 by 1, or should we divide 1 by 3 first?

To remove the ambiguity, we need to use parentheses to clarify the order of operations. If the expression is supposed to be (9-3)/(1/3)+1, the answer would be:

(9-3)/(1/3)+1 = 6 / (1/3) + 1 = 6 * 3 + 1 = 19

However, if the expression is supposed to be 9 - 3/(1/3) + 1, the answer would be:

9 - 3/(1/3) + 1 = 9 - 3*3 + 1 = 1

So, the final answer depends on the intended order of operations, which should be made clear with the use of parentheses.